Dissolved Po-210 and Pb-210 in Guarani aquifer groundwater, Brazil - Bonotto, Daniel Marcos [UNESP]; Caprioglio, L. [UNESP]; Bueno, T. O. [UNESP]; Lazarindo, J. R. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2009)
The huge Guarani aquifer located in the South American continent is a very important resource for the region, and its drinking water quality has been investigated according to international standards, inclusive radiological parameters. This paper describes Po-210 and Pb-210 activity concentration data in groundwater samples collected at the Brazilian portion of Guarani aquifer, that is characterized by a great variability of temperature (18-70 degrees C), pH (4.0-9.9), sodium content (0.3-322 mg/l), bicarbonate content (0.1-318 mg/l), etc. Non-expensive alpha counting following some radiochemical steps for extracting and depositing dissolved Po-210 was used. The results of the measurements for samples collected in duplicate yielded a maximum Po-210 activity concentration of 3.7 mBq/L and a maximum Pb-210 activity concentration of 6.7 mBq/l, that are values greatly lower than the guidance level of 0.1 Bq/l established by the WHO for their presence in drinking water. The high sensitivity of the method allowed its applicability on the identification of complexes geochemical and hydrogeological processes occurring in Guarani aquifer as well on the evaluation of the drinking water quality in terms of dose calculations. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Po-210 and Pb-210 activity concentration; Groundwater radioactivity; Guarani aquifer; Drinking water quality; Dose calculations